Evaluation of Delayed Puberty of Patients with Beta Thalassemia Major in –Diyala Governorate - Alaa A Mahmud; Ali M Al-Gharawi; Falah M Mustafa (Diyala Journal of Medicine, 2018)
Background: The absence of secondary sexual characteristics are known complications in patients with beta thalassemia major.